Exogenous melatonin enhances cell wall response to salt stress in common bean (Phaseolus vulgaris) and the development of the associated predictive molecular markers - Zhang, Qi; Qin, Bin; Wang, Guang-da; Zhang, Wen-jing; Li, Ming; Yin, Zhen-gong; Yuan, Xiankai; Sun, Hao-yue; Du, Ji-dao; Du, Yan-li; Jia, Pengyu (Frontiers in Plant Science, 2022)
Common bean is an important food crop. Salt stress can inhibit seed germination, promote senescence, and modify cell wall biosynthesis, assembly, and architecture. Melatonin, an indole heterocycle, has been demonstrated to greatly impact cell wall structure, composition, and regulation in plants under stress. However, the molecular basis for such assumptions is still unclear. In this study, a common bean variety, “Naihua” was treated with water (W), 70 mmol/L NaCl solution (S), and 100 μmol/L melatonin supplemented with salt solution (M+S) to determine the response of common bean to exogenous melatonin and explore regulatory mechanism of melatonin against salt stress. The results showed that exogenous melatonin treatment alleviated salt stress-induced growth inhibition of the common bean by increasing the length, surface area, volume, and diameter of common bean sprouts. Moreover, RNA sequencing (RNA-seq) and real-time quantitative PCR (qRT-PCR) indicated that the cell wall regulation pathway was involved in the salt stress tolerance of the common bean enhanced by melatonin. Screening of 120 germplasm resources revealed that melatonin treatment improved the salt tolerance of more than 65% of the common bean germplasm materials. Melatonin also up-regulated cell wall pathway genes by at least 46%. Furthermore, we analyzed the response of the common bean germplasm materials to melatonin treatment under salt stress using the key genes associated with the synthesis of the common bean cell wall as the molecular markers. The results showed that two pairs of markers were significantly associated with melatonin, and these could be used as candidate markers to predict whether common bean respond to exogenous melatonin and then enhance salt tolerance at the sprouting stage. This study shows that cell wall can respond to exogenous melatonin and enhance the salt tolerance of common bean. The makers identified in this study can be used to select common bean varieties that can respond to melatonin under stress. Overall, the study found that cell wall respond melatonin and enhance the salt tolerance and developed the makers for predicting varieties fit for melatonin under stress in common bean, which may be applied in the development of common bean varieties with abiotic stress tolerance.